2008
DOI: 10.1039/b719552d
|View full text |Cite
|
Sign up to set email alerts
|

Aminotroponiminate calcium and strontium complexes

Abstract: Heteroleptic aminotroponiminate complexes of calcium and strontium have been prepared. The monomeric calcium complex [((iPr)2ATI)CaI(THF)3] 1 ((iPr)2ATI = N-isopropyl-2-(isopropylamino)troponiminate) and the corresponding dimeric strontium compound [( (iPr)2ATI)SrI(THF)2]2 2 were obtained by reaction of [((iPr)2ATI)K] and MI2. Whereas the mixed ligand compound of composition [((iPr)2ATI)Ca(iPrAT)]2 3 (iPrAT = 2-(isopropylamino)troponate) was not obtained via a salt metathesis but by reaction of [Ca(N(SiMe3)2)2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 18 publications
1
25
1
Order By: Relevance
“…ATI complexes [M(ATI i Pr/ i Pr ){N(SiMe 3 ) 2 (thf) 2 }] ( 25‐M ) of the heavier alkaline earth metals Ca and Sr have been tested as catalysts in intramolecular hydroamination reactions and compared to their Yb II analogs (Scheme ) . The ATI ligand presumably serves as a spectator ligand in these transformations, while the {N(SiMe 3 ) 2 } – group undergoes transamination with the substrate 23 .…”
Section: Catalysismentioning
confidence: 99%
“…ATI complexes [M(ATI i Pr/ i Pr ){N(SiMe 3 ) 2 (thf) 2 }] ( 25‐M ) of the heavier alkaline earth metals Ca and Sr have been tested as catalysts in intramolecular hydroamination reactions and compared to their Yb II analogs (Scheme ) . The ATI ligand presumably serves as a spectator ligand in these transformations, while the {N(SiMe 3 ) 2 } – group undergoes transamination with the substrate 23 .…”
Section: Catalysismentioning
confidence: 99%
“…In line with the findings of Hultzsch and coworkers for lanthanide(III) systems ( Gribkov et al 2006), it was suggested that both substrate and product inhibit the reaction to similar extents; hence, reaction-rate constants are dependent upon the substrate concentration at t o . While Crimmin et al refrained from application of heavier analogues of 1 and 2 (M = Sr, Ba; Avent et al 2005b) in hydroamination catalysis owing to their propensity to undergo Schlenk-like redistribution under the reaction conditions, Datta et al (2007Datta et al ( , 2008a reported aminotroponoate and aminotroponiminate supported calcium and strontium amide complexes 3-5 as competent catalysts for the intramolecular hydroamination of aminoalkenes (figure 9). Although, in most instances, selectivities and catalyst activities were commensurate with those reported for the b-diketiminato-stabilized calcium amide 1, it is noteworthy that Datta et al reported not only that 4 mol% 4 was effective for the intramolecular hydroamination of an aminoalkyne to the corresponding imine in more than 90 per cent after 22 h at room temperature, but also that both 4 and 5 affect the cyclization of the internal (activated) alkene trans-1-amino-2,2-dimethyl-5-phenyl-4-pentene to the corresponding pyrrolidine in 80 per cent yield after 10 min at room temperature (figure 10).…”
Section: (B) the Schlenk Equilibriummentioning
confidence: 99%
“…Three oxygen molecules from THF occupy the three sites, two N atoms from the amidinato ligand occupy two sites, and the I ligand fills the remaining coordination site. The Ca–I bond length is of 3.084(3) Å, which is shorter than those in G (3.1365(8) Å and 3.1533(8) Å), Westerhausen′s [(thp) 4 Ca(I)(CH 2 SiMe 3 )] (thp=tetrahydropyrran) (3.191(3) Å), and the average Ca–I bond distances in A (3.144 Å), and C (3.106 Å) . The decrease in the bond length is most likely a result of slightly increased donor ability of the amidinates relative to the β ‐diketiminates as well as a weak steric shielding of the calcium center by the ligands.…”
Section: Resultsmentioning
confidence: 82%